The EEC Commission and the negotiations for a trade agreement with Israel, 1958–1964. Issue 7 (9th November 2016) - Heimann, Gadi
Abstract: This article examines the role played by the European Commission in negotiations between the European Economic Community and Israel concerning a trade agreement. It demonstrates that the Commission's attitude to such an agreement was far more positive than that of the six member states. The Commission's leadership pushed the Israelis into pursuing an association agreement, and when this was revealed to be impossible, it took a leading role in concluding a more limited trade agreement. The Commission's proposal formed the basis for the final agreement, which took shape in 1964. The article attempts to discern the motives behind the Commission's behaviour; its central claim is that the Commission's leadership viewed negotiations with Israel and the conclusion of an agreement as a means to achieve their ideological and institutional goals.